“I would be very proud to be part of an initiative that didn’t exclude people because it was hard”: mapping and contextualising health equity responsibilities and decision-making tensions in the implementation of a multi-level system reform initiative - Tristan Bouckley; David Peiris; Devaki Nambiar; Samuel Prince; Sallie-Anne Pearson; Gill Schierhout (International Journal for Equity in Health, 2025)
Abstract Background Health systems face competing demands when implementing health sector reforms. While health equity principles are generally promoted during reform discussions, they are often deprioritised during implementation. This qualitative study aimed to (1) identify how implementers and designers expected health equity to be included in the implementation of a place-based health system reform initiative, and (2) identify factors that influenced prioritisation of health equity during early implementation. Method We conducted eighteen semi-structured interviews in 2022 and 2023 with a purposive sample of senior policy executives, programme managers and clinicians involved in the design and early implementation of a place-based health system reform initiative in New South Wales, Australia. Informed by a grounded approach, data were analysed inductively drawing on a constant comparative approach. Emerging health equity definitions and expectations informed the development of a Theory of Change (ToC) articulating participants’ expectations about how health equity was intended to be embedded in the programme. We also identified opportunities and challenges to prioritise action to address health equity throughout implementation, which informed critical appraisal of the ToC. Results We identified diffuse actions and responsibilities to address health equity in this state-wide, place-based health reform, articulating these actions and responsibilities in a ToC. This showed diffuse responsibilities for health equity across system levels. We also identified six critical decision-making tensions that influenced health equity prioritisation during early implementation, reflecting participants’ perceptions that health equity prioritisation was in conflict with attention to other priorities. These were equity-efficiency; localisation-capacity for health equity; diffuse responsibilities-enforceability; invisible-vocal sub-populations; and health equity-sustainable business models for private providers. Conclusion The distribution of heath equity responsibilities, as we demonstrated through a ToC of a decentralised, place-based reform, present risk to health equity prioritisation. Risks were particularly present when local resourcing and capacity were stretched, and limited policy guardrails were in place to counteract decision-making tensions, such as clear health equity accountabilities, responsibilities, and actions.